DYNAMICS OF DEMAND FOR BIOPESTICIDE PRODUCTS AND ITS KEY DETERMINANTS - Zenita Afifah Fitriyani; Dimas Ganda Permana Putra; Mega Darmi Novita (Creative Research Management Journal, 2025)
The growth of the organic market and the demand for residue reduction are driving the need for environmentally friendly inputs, but biopesticide adoption at the farmer level remains limited. This study analyzes the dynamics of biopesticide demand by assessing the impact of willingness to pay (WTP), operational performance, and the Go Organic Program in two agroecological contexts: Bendunganjati Village (Pacet) and Randugenengan Village (Dlanggu). The research design was a quantitative explanatory survey (cross-sectional) using stratified random sampling. The instruments were validated and reliable. The analysis used multiple linear regression to test the influence of explanatory factors on demand and usage intensity, and an exponential smoothing approach to predict monthly demand. The results show that Willingness to Pay has a positive and significant effect on demand, the Go Organic Program has a negative and significant effect, indicating a possible substitution to biopesticide production practices, while operational performance is positive but not significant. The model is simultaneously significant, indicating that the variation in demand is explained by the three variables. For forecasting, a larger alpha provides the closest trace to the actual data and produces more accurate predictions for the following period than a smaller alpha. These findings confirm that strengthening WTP based on evidence of efficacy and redesigning the implementation of the Go Organic Program to encourage, rather than substitute, commercial demand is more crucial than operational improvements alone. Managerial recommendations include measurable demonstration plots, packaging economy, visual SOPs, stock and lead time management, and the integration of biopesticide materials into the Go Organic Program module.